Morbidity profile and prevalence of postoperative complications among patients after a short-term surgical mission in a district hospital in Ghana: Short-term surgical mission in a district hospital - Gyakobo, Mawuli Kotope; Engmann, Stephen Tetteh; Amponsah-Manu, Forster; Kwansa, Irene Manubea; Arkorful, Temitope; Attuah, Samuel; Brown, Frank Ewusie; Kpormegbe, Sefakor Juliet; Mayeden, Samuel Yao; Awoonor-Williams, Koku (Journal of Surgery and Medicine, 2026)
Background/Aim: In most of Africa, including Ghana, access to surgical care is limited by socioeconomic factors, infrastructural constraints, and shortages in human resources. Short-term surgical missions (STSMs) have been used to bridge this gap by providing free surgical services, especially in rural areas. This study aimed to determine the morbidity profile and prevalence of postoperative complications among patients who underwent surgery during an STSM at a municipal hospital in the Volta Region of Ghana. Methods: This cross-sectional descriptive study involved a secondary analysis of data from 180 patients who underwent surgical procedures during an STSM at Ketu North Municipal Hospital, Volta Region, Ghana, from October 27 to November 2, 2024. The mission was conducted by a local team of 38 health professionals, including surgeons, nurses, and anesthetists. Patients’ selection was based on predetermined criteria. Results: The mean age of the patients was 45.7 (18.7) years, with a range of 2 to 82 years. Most patients were male (54.4%). Surgical care was provided for general surgical and gynecologic conditions. Inguinal hernia was the most common diagnosis (35.0%), with right-sided hernia being the predominant type, followed by lipoma (24.4%) and goiter (15.6%). Spinal anesthesia was the most frequently used anesthetic technique (47.8%). A low complication rate of 1.0% was observed, consisting mainly of urinary retention and pruritus. Conclusion: Short-term surgical missions can effectively address surgical needs in low-resource settings such as rural Ghana by providing safe surgical care with minimal complications. These findings underscore the importance of a well-organized mission and sustainable local partnerships to improve access to surgical care and patient outcomes.